2018
DOI: 10.1002/jcb.27915
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and prognostic significance of YWHAZ in non‐small–cell lung cancer patients: Immunohistochemical analysis

Abstract: YWHAZ has been suggested to as an oncogene in various human malignancies, including non‐small–cell lung cancer (NSCLC). Our study presents more evidence to confirm the clinical significance and biological function of YWHAZ in NSCLC. In our results, YWHAZ was upregulated in lung squamous cell carcinoma tissues and lung adenocarcinoma tissues through analyzing The Cancer Genome Atlas (TCGA) database, and confirmed high levels of YWHAZ messenger RNA and protein in lung squamous cell carcinoma tissues and lung ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…As can be seen in Figure 3A and Figure 4A, YWHAZ expression was significantly correlated with overall survival at 60 months in LIHC (p = 0.0197) and LUAD (p = 0.016), and with disease-free survival at 60 months in BRCA (p = 0.0279) and LUAD (p = 0.016). We also conducted Kaplan-Meier survival analysis in Gene Expression Profiling Interactive Analysis (GEPIA) database with larger samples [77], determining that overall survival time was remarkably longer in LIHC (p = 0.016) and LUAD (p = 0.00023) with low YWHAZ expression ( Figure 3B) [24], which was consistent with the result of TCGA. However, there was no statistic difference of disease-free survival between high YWHAZ and low YWHAZ samples ( Figure 4B).…”
Section: Prognosissupporting
confidence: 76%
See 2 more Smart Citations
“…As can be seen in Figure 3A and Figure 4A, YWHAZ expression was significantly correlated with overall survival at 60 months in LIHC (p = 0.0197) and LUAD (p = 0.016), and with disease-free survival at 60 months in BRCA (p = 0.0279) and LUAD (p = 0.016). We also conducted Kaplan-Meier survival analysis in Gene Expression Profiling Interactive Analysis (GEPIA) database with larger samples [77], determining that overall survival time was remarkably longer in LIHC (p = 0.016) and LUAD (p = 0.00023) with low YWHAZ expression ( Figure 3B) [24], which was consistent with the result of TCGA. However, there was no statistic difference of disease-free survival between high YWHAZ and low YWHAZ samples ( Figure 4B).…”
Section: Prognosissupporting
confidence: 76%
“…Deng Y et al reported that YWHAZ mRNA and protein expression was significantly higher in 152 non-small cell lung cancer (NSCLC) tissues compared to 30 noncancerous lung tissues by qRT-PCR and IHC [24]. Using western blot, Zhao G-Y et al also detected higher YWHAZ expression in 16 NSCLC tissues than in matched adjacent tissues [25].…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ) was identified in 55.9% of all patients’ combinations from all nine cancer types. This protein is present in high levels in different cancer cells and is associated with tumor cell proliferation, cell invasion and migration, and drug resistance (Nishimura et al, 2013; Hong et al, 2018; Deng et al, 2019). This protein target has prognostic potential, and its overexpression is associated with short OS time in non-squamous-cell lung carcinoma (Deng et al, 2019); its knockdown has suppressed tumorigenesis in ovarian cancer cells (Hong et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…At present, many studies have indicated that the 14-3-3 protein plays an oncogenic role in many kinds of tumors and inhibits apoptosis [20,[28][29][30]. Therefore, we focused on monitoring the expression level of apoptosis-related proteins after stable overexpression of LNK.…”
Section: Discussionmentioning
confidence: 99%